Spawn and Reproduction of the Gastropod Trochita pileus (Lamarck, 1822) from the Southwestern Atlantic Ocean - Torroglosa, Maria Eugenia (2012)
Specimensand eggs masses of the gastropodTrochita pileus were collectedduring a researchcruise by bottom trawling at depths between 82 m and 120 m. Adult T. pileus were found attachedto hard substrates,such as the shells of scallopsand oysters. The egg mass of T. pileus is composed of 7-8 transparent, triangularshaped egg capsulesfixed to the substrate with stalks. Four egg masses collected from brooding females, with a total number of 241 embryos,were examined. T. pileus is a protandrous hermaphrodite, and histological studies of the male, transitional, and female gonads were performed.The testicular portion of the gonad in both male and transitional individuals and the ovary of the female were studied by histological techniques. Spermatogenesis was observed for males and transitional individuals.